Multimodal approach to pain management in thoracic surgery - Poniatovska, H.; Dubrov, S. (General Surgery, 2023)
The American Cancer Society estimated that 68,820,000 men and 61,360,000 women in the United States of America would die from lung and bronchial cancer in 2022, which is equal to 21% of all cancer deaths. Patients who undergo thoracotomy have a higher risk of postoperative complications due to the severe pain syndrome that typically develops after surgery. Even though there has been extensive research on the advantages and disadvantages of various perioperative analgesia techniques, the search for the best and safest still continues. Objective — to improve the results of perioperative anesthesia in patients undergoing thoracotomy by choosing the optimal method of analgesia. Materials and methods. A total of 59 patients with lung cancer who underwent thoracotomy at the communal non‑profit enterprise «Kyiv City Clinical Hospital No 17» from 2018 to 2020 were included in an open‑label noncommercial randomized controlled clinical trial. Patients were divided into 2 groups: the multimodal analgesia (MA) group (32 patients) and the epidural analgesia (EA) group (27 patients). According to the concept of preemptive analgesia, patients in the MA group received 1000 mg of paracetamol and 50 mg of dexketoprofen intravenously 1 hour before surgery. In the postoperative period, dexketoprofen and paracetamol were administered every 8 hours in combination with epidural analgesia. During postoperative epidural analgesia, patients received 40 mg of a 2% lidocaine solution through a catheter inserted into the epidural space (Th5—Th6) and a ropivacaine 2 mg/mL (3—14 mL/h) infusion. Patients in the EA group received only epidural analgesia in the postoperative period. After placement of an epidural catheter in the epidural space (Th5—Th6), they had an injection of 40 mg of a 2% lidocaine solution and an epidural infusion of ropivacaine 2 mg/ml (3—14 mL/h). Results. The study groups did not demonstrate a statistically significant difference in terms of age, hight, weight, a grade of anesthesiological risk (ASA), blood loss, surgery duration, and surgical volume (р >0,05). The level of analgesia was assessed using the numerological rating scale (NRS) after 3, 6, 24, and 32 hours after surgery. Every research stage revealed a significant difference in the level of pain syndrome between the study groups (p<0.05). Patients in the EA group experienced more severe pain syndrome than those in the MA group. Consequently, 7 patients (26%) in the EA group were anesthetized with morphine 10 mg intramuscularly compared to 3 patients (9%) in the MA group. Conclusions. In patients undergoing thoracic surgery, a multimodal analgesic approach, which includes the use of COX‑2 and COX‑3 inhibitors in combination with epidural analgesia, has been shown to produce better analgesia compared to epidural anesthesia alone. The beneficial effect of multimodal analgesia was seen in a significant difference (p<0.05) in the intensity of pain syndrome between the study groups in the early postoperative period after thoracotomy.